The Experimental Effect of Parental Attentiveness on Children's Physical Activity Behavior - Michael J. Rebold; Mallory S. Kobak; Cody A. Croall; Emily A. Cumberledge; Melanie Hall; Lindsey Raumikaitis (Asian Society of Kinesiology, 2021)
OBJECTIVES To assess children's physical and sedentary activity behavior, enjoyment (i.e., liking), and preference during two separate experimental conditions: parent attentive and parent non-attentive. METHODS Ten children (n = 6 boys, 4 girls), 3 to 6 years old, along with one parent (n = 6 mothers, 4 fathers) per child participated in each condition on separate days for 30-minutes in which they could choose from a variety of physical and/or sedentary activities. RESULTS A greater number of accelerometer counts (p = 0.04) were accumulated during the parent attentive (96,547 ± 33,075.26 counts) condition than the parent non-attentive (48,316.30 ± 46,101.47 counts) condition. More time (p = 0.007) was allocated to sedentary activities during the parent non-attentive (19.5 ± 13.3 minutes) condition than parent attentive (2.8 ± 3.55 minutes) condition. Children liked (p = 0.004) the parent attentive (9.05 ± 1.21 cm) condition more than parent non-attentive (4.42 ± 3.18 cm) condition. A non-significant (p = 0.21) proportion of children identified the parent attentive (70%) as their preferred condition over the parent non-attentive condition. CONCLUSIONS Parental attentiveness may be an important component to take into consideration when trying to maximize children's physical activity behavior and enjoyment while simultaneously reducing sedentary behavior.